Genome-wide analysis of HECT E3 ubiquitin ligase gene family in Solanum lycopersicum - Bhaskar Sharma (Nature Portfolio, 2021)
Abstract The E3 ubiquitin ligases have been known to intrigue many researchers to date, due to their heterogenicity and substrate mediation for ubiquitin transfer to the protein. HECT (Homologous to the E6-AP Carboxyl Terminus) E3 ligases are spatially and temporally regulated for substrate specificity, E2 ubiquitin-conjugating enzyme interaction, and chain specificity during ubiquitylation. However, the role of the HECT E3 ubiquitin ligase in plant development and stress responses was rarely explored. We have conducted an in-silico genome-wide analysis to identify and predict the structural and functional aspects of HECT E3 ligase members in tomato. Fourteen members of HECT E3 ligases were identified and analyzed for the physicochemical parameters, phylogenetic relations, structural organizations, tissue-specific gene expression patterns, and protein interaction networks. Our comprehensive analysis revealed the HECT domain conservation throughout the gene family, close evolutionary relationship with different plant species, and active involvement of HECT E3 ubiquitin ligases in tomato plant development and stress responses. We speculate an indispensable biological significance of the HECT gene family through extensive participation in several plant cellular and molecular pathways.